Economics, Entrepreneurship and Utopia: The Economics of Jeremy Bentham and Robert Owen by Estrella Trincado and Manuel Santos-Redondo. Routledge. 2018. 198 páginas. ISBN: 978-03-67876-42-5. - Menudo, José Manuel (Iberian Journal of the History of Economic Thought, 2020)
Reseña del libro de Estrella Trincado y Manuel Santos-Redondo, Economics, Entrepreneurship and Utopia: The Economics of Jeremy Bentham and Robert Owen. Routledge. 2018. 198 páginas. ISBN: 978-03-67876-42-5.